Antimetastatic effects of Eclipta prostrata extract on oral cancer cells. Issue 9 (2nd July 2018) - Liao, Miao‐Yu; Chuang, Chun‐Yi; Hsieh, Ming‐Ju; Chou, Ying‐Erh; Lin, Chiao‐Wen; Chen, Wen‐Rong; Lai, Chih‐Ting; Chen, Mu‐Kuan; Yang, Shun‐Fa
Abstract: Eclipta prostrata, a traditional Chinese medication, has been used for the treatment of several diseases. However, the molecular mechanism underlying the effects of Eclipta prostrata extracts (EPE) on human oral cancer cell metastasis remains unclear. We thus examined the effects of EPE on metastasis promoting proteins in oral cancer. Our results revealed that the EPE attenuated SCC‐9, HSC‐3, and TW2.6 cell migration and invasiveness by reducing matrix metalloproteinase (MMP)‐2 enzyme activities. In addition, Western blot analysis revealed that EPE significantly reduced the levels of phosphorylated extracellular signal‐regulated kinase 1/2 (ERK 1/2) but not those of c‐Jun N‐terminal kinase (JNK) 1/2 and p38. In conclusion, we found that EPE could inhibit oral cancer metastasis through the inhibition of MMP‐2 expression. Therefore, EPE may be used to prevent the metastasis of oral cancer, and has the potential to be applied to cancer treatment.